Effect of Tow Duration and Speed on the Capture Efficiency of Bottom Trawl - V.R, Madhu; S.K., Panda (Fishery Technology, 2025)
The catching performance of a 34 m High opening bottom trawl (HOBT) was studied with tow durations of 15, 60 and 120 min each and with two towing speeds (0.87Â± 0.03 and 1.36 + 0.03 ms"1) to find out changes in the species retention and escapement in terms of weight and number from the codend. Variations in the retention and escapement catch per unit effort (CPUE) in terms of weight and number for the different tow durations were compared. Although, the mean catch rate expressed as mean CPUE was found to be consistently higher in the 15-min haul, the difference was not statistically significant from that of 60 and 120-min hauls. Within and between hauls variation in catch rate of six species (as determined by SIMPER analysis) was studied using univariate GLM with tow duration and speed as categorical predictors. The catch rates of three species Trichiurus lepturus, Lactarius lactarins and Uroteuthis (Photololigo) duvauceli were found to be significantly different due to tow duration effect, but neither speed nor the interaction effect had any significant effect on the catch rates for these species. The mean diversity, dominance and evenness indices showed no significant difference among the hauls of different tow durations. Based on the results of the study, it is concluded that the short duration tows of 15-min are as effective as the 60 and 120- min tows- for estimating catch per unit effort in terms of total weight, number and diversity indices. Keywords: tow duration, retention